P547 Relationship length of gay male couples and sexually transmitted infections. (14th July 2019) - Qquellon, Luz; Vargas, Silver; Calvo, Gino; Diaz, David; Navarro, Javier; Lugo, Elizabeth; Reyes-Díaz, Michael; Konda, Kelika
Abstract : Background: Bacterial sexually transmitted infections (STIs) are preventable, treatable, and have been increasing among men who have sex with men due to limited STIs/HIV screening and high-risk sexual behaviors, including partner concurrency and condomless anal sex. Within stable relationships, sexual behavior patterns may change over time. This analysis was conducted to estimate if relationship length is associated with STIs prevalence among gay men couples. Methods: Gay men who reported having a primary relationship answered a survey and were tested for bacterial STIs (syphilis, chlamydia or gonorrhea) during 2015 in Lima, Peru. Among couples, discordant STI status (only one partner had an STI) and concordant status (both partners had the STI) were compared by STI. Generalized linear models, controlling for correlation between couple members, were used to estimate adjusted prevalence ratios (aPRs). Results: Overall, 254 individuals were included (98 couples and 58 one partner only). Median age was 26 years (IQR: 22–30), 62 individuals (24.4%) reported sex outside their relationship and 76 (29.9%) were diagnosed with at least one bacterial STI. Regarding relationship length, 86 (33.9%) had been in their current relationship <6 months, 86 (33.9%) between 6–18 months, and 78 (30.7%) for 18+ months. Among the 98 couples, more couples had discordant STI status than concordant status for syphilis (12.8% vs 4.3%, p=0.001), chlamydia (25.0% vs 7.6%, p<0.001) and gonorrhea (20.7% vs 2.2%, p<0.001). Having a relationship for 18+ months was negatively associated with STI prevalence (aPR: 0.55, 95% CI: 0.30–0.98) after adjusting for age, HIV status, use of condom, and anal intercourse outside primary relationship. Conclusion: Our data suggest STIs prevalence is lower among gay men in longer term relationships. Future studies on gay male couples should consider the effect of relationship length on sexual behavior patterns to implement interventions for reducing STIs occurrence based on findings in a gay couple context. Disclosure: No significant relationships.